2013
DOI: 10.1186/1743-7075-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid and melatonin ameliorate carbon tetrachloride-induced hepatic injury, oxidative stress and inflammation in rats

Abstract: This study investigated the protective effects of melatonin and folic acid against carbon tetrachloride (CCl4)-induced hepatic injury in rats. Oxidative stress, liver function, liver histopathology and serum lipid levels were evaluated. The levels of protein kinase B (Akt1), interferon gamma (IFN-γ), programmed cell death-receptor (Fas) and Tumor necrosis factor-alpha (TNF-α) mRNA expression were analyzed. CCl4 significantly elevated the levels of lipid peroxidation (MDA), cholesterol, LDL, triglycerides, bili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 54 publications
7
61
0
1
Order By: Relevance
“…As a result, fewer fatty acids for the production of cholesterol, triglyceride, and LDL are transported to the liver, resulting in reduced synthesis of the lipids. These results are consistent with findings from experimental models treated simultaneously with carbon tetrachloride and folic acid [26]. A reduction in serum cholesterol levels can result in a decrease in intra-hepatic circulation of bile acids and prevent production of excessive bile [37].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As a result, fewer fatty acids for the production of cholesterol, triglyceride, and LDL are transported to the liver, resulting in reduced synthesis of the lipids. These results are consistent with findings from experimental models treated simultaneously with carbon tetrachloride and folic acid [26]. A reduction in serum cholesterol levels can result in a decrease in intra-hepatic circulation of bile acids and prevent production of excessive bile [37].…”
Section: Discussionsupporting
confidence: 82%
“…It has been found that leukocytes, potentially by producing pro-fibrotic mediators such as TGF-β1, affects HSCs and enhances ECM synthesis in various liver diseases [24]. Folic acid plays an important role as a potent antioxidant by scavenging free radicals and reducing oxidative stress, [25] to reduce the hepatic tissue damage in rats treated with carbon tetrachloride, [26] receiving a high-fat diet, [17] under chronic treatment with ethanol, [27] and receiving methotrexate [12]. Studies have shown that antioxidant supplements can significantly inhibit hepatic necrosis [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of fibrotic septa and increase in enzyme levels were impaired in animals treated with melatonin (5 and 10 mg/kg body weight), which is in line with previous reports on the effect of the pineal hormone in mice or rats with CCl 4 -induced fibrosis. [16][17][18][19][20][21][22] The critical step in the generation of liver fibrosis is the activation of HSCs resulting in a-SMA and collagen deposition. 28 The increased a-SMA expression in the livers of CCl 4 -treated mice was significantly diminished by melatonin administration, as indicated by immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…15 Using this toxinmediated model, it has been found that melatonin administration, at doses ranging from 2.5 to 20 mg/kg body weight, prevents liver histopathologic changes, reduces hepatic hydroxyproline content, inhibits oxidative stress and apoptosis, increases antioxidant enzyme levels, or reduces proinflammatory cytokine production, when administered intraperitoneally to rats or mice. [16][17][18][19][20][21][22] However, in these in vivo studies, effects of melatonin on the activation of HSCs and changes in the expression of fibrogenic factors or molecules involved in ECM degradation have not been tested. Moreover, because melatonin was always given before or in parallel to CCl 4 administration, only a preventive effect before the onset of liver toxicity was demonstrated.…”
mentioning
confidence: 99%